The Influence of Transformational Leadership Style on Employee Performance with Work Engagement as Mediation - Yohana, Yohana; Ridho, Fajar; Malik, Malik; Dasman, Sunita; Daspar, Daspar (Review: Journal of Multidisciplinary in Social Sciences, 2024)
Transformational leadership style is one of the leadership styles needed in companies. Leadership is also an important factor so that employees can continue to improve their performance. A leader must also be able to increase work motivation and be able to instill a sense of pride in his work in his employees, because by having motivation and being proud of what we are doing, employees will work well and produce maximum work results. The methodology in this research is quantitative research with a random sampling data collection method at the Al-Fath Collection Karawang company which operates in the garment sector. For the data analysis method it is processed using PLS with the help of the SMARTPLS 3.0 application. The aim of this research is to determine the influence of transformational leadership on employee performance, to determine the influence of transformational leadership on work engagement, and to determine the influence of transformational leadership style on employee performance and work engagement on employee performance. The results of this research indicate that the transformational leadership style cannot directly influence employee performance, but the transformational leadership style can indirectly influence employee performance.